FLUID–ROCK INTERACTION AT A CARBONATITE-GNEISS CONTACT, ALNÖ, SWEDEN - Skelton A.; Hode vuorinen J.; Arghe F.; Fallick A. (My University, 2007)
We evaluate balanced metasomatic reactions and model coupled reactive and isotopic transport at a carbonatite-gneiss contact at Alnö, Sweden. We interpret structurally channelled fluid flow along the carbonatite-gneiss contact at ∼640°C. This caused (1) metasomatism of the gneiss, by the reaction: , (2) metasomatism of carbonatite by the reaction: calcite + SiO2 = wollastonite + CO2, and (3) isotopic homogenization of the metasomatised region. We suggest that reactive weakening caused the metasomatised region to widen and that the metasomatic reactions are chemically (and possibly mechanically) coupled. Spatial separation of reaction and isotope fronts in the carbonatite conforms to a chromatographic model which assumes local calcite–fluid equilibrium, yields a timescale of 102–104 years for fluid–rock interaction and confirms that chemical transport towards the carbonatite interior was mainly by diffusion. We conclude that most silicate phases present in the studied carbonatite were acquired by corrosion and assimilation of ijolite, as a reactive by-product of this process and by metasomatism. The carbonatite was thus a relatively pure calcite–H2O−CO2–salt melt or fluid.
Keywords: Carbonatite; Fluid flow; Metasomatism